Teaching English following learner-based model - Elena G. Kashina; Tatjana I. Rudneva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
When Russia entered international education space, it caused the necessity to analyse the most important spheres in the field of students’ professional training and it had to change the format of education in the humanities, which has to be in line with the demand of the state and the requirement of each individuality. The time has come to understand the education process as reflective and developing space, which provides good quality of university graduates. In the process of social services commissioning. And at this time the role of a foreign language becomes very important which guarantees successful professional activity. This article deals with learner based teaching which gives support in the process of defining the goals of teaching. Communicative education gives an opportunity for active speech practice involving students in various role situations. It becomes actual to use multirole methods to involve students in dialogues and situations. Based on experimental material it is proved that teachers have to be good actors, it is especially important for teachers of foreign languages. It is proved that drama as the art of actions defines a new style of teaching a foreign language.